(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The phenomenon of excessive engine smoking in cars is a serious problem that not only affects the performance of the vehicle but also presents a significant risk to the environment and public safety. It is frequently caused by underlying mechanical failures, such as worn-out piston rings, malfunctioning valve seals, or clogged air filters, which allow fuel, oil, or coolant to burn within the engine. On the other hand, excessive engine smoke can lead to serious engine damage, decreased fuel economy, and increased emissions of dangerous pollutants if ignored. The study aims to identify the main factors causing excessive engine smoke, evaluate the effects on vehicle safety and environmental sustainability, and provide practical solutions. The paper also examines typical engine components and diagnostic techniques to emphasize preventative maintenance strategies, including using cleaner fuels, changing oil on time, and performing routine engine inspections. It also looks at innovative remedies, such switching to low-emission vehicles and sustainable automobile technology that lessen environmental impact. In addition to being essential for road safety, making sure automobile engines are operating properly is a critical first step in developing sustainable transportation.